Simulation and Analysis of Multi-sluice Dam Channel Flow Evolution Based on MIKE11 - ZHANG Shixin; ZHANG Jing (Renmin Zhujiang)
Due to the influence of sluices,the flow propagation law of multi-sluice dam is complicated,which brings great difficulties to the forecast of river flow and water dispatching.In this paper,the river channel of Qipanshan Reservoir and Tuanjie Sluice of Puhe River is taken as the research object,and the river is divided into seven sections.On the basis of the MIKE11HD construction,the influence of multi-sluice dams on river flow evolution is analyzed,and the change of peak discharge travel time and flow attenuation in different sections is studied by the model.The results show that there is a significant power function relationship between the flood peak discharge and the travel time.As the flood peak discharge is larger,the travel time will be shorter.The attenuation rate per kilometer is related to the characteristics of the channel and the vegetation on both sides of the channel.Under the influence of artificial channelization,the discharge attenuation rate per kilometer is minimum in the sluice 7-sluice 6 section,and maximum in the section of the rubber dam on the sluice to Laoshiniu rubber dam.This study can provide a basis for the joint operation of multi-sluice dam in the ecological corridor of Puhe River,and also provide a reference for the flow simulation and flood forecast of other multi- sluice dam channels.